Malignancies in the rheumatoid arthritis abatacept clinical development programme: an epidemiological assessment. Issue 12 (3rd December 2008) - Simon, T A; Smitten, A L; Franklin, J; Askling, J; Lacaille, D; Wolfe, F; Hochberg, M C; Qi, K; Suissa, S
Abstract : Objective: To provide context for the malignancy experience in the rheumatoid arthritis (RA) abatacept clinical development programme (CDP) by performing comparisons with similar RA patients and the general population. Methods: Malignancy outcomes included total malignancy (excluding non-melanoma skin cancer (NMSC)), breast, colorectal, lung cancers and lymphoma. Comparisons were made between the observed incidence in patients within the abatacept CDP and RA patients on disease-modifying antirheumatic drugs (DMARD) identified from five data sources: the population-based British Columbia RA Cohort, the Norfolk Arthritis Register, the National Data Bank for Rheumatic Diseases, the Sweden Early RA Register and the General Practice Research Database. Age and sex-adjusted incidence rates (IR) and standardised incidence ratios (SIR) were used to compare events in the abatacept trials with the RA DMARD cohorts and the general population. Results: A total of 4134 RA patients treated with abatacept in seven trials and 41 529 DMARD-treated RA patients in the five observational cohorts was identified for study inclusion. In the abatacept-treated patients, the 51 malignancies (excluding NMSC), seven cases of breast, two cases of colorectal, 13 cases of lung cancer and five cases of lymphoma observed were not greater than the range of expected cases from the five RA cohorts. The SIR comparing RA patients with the general population were consistent with those reported in the literature. Conclusions: The IR of total malignancy (excluding NMSC), breast, colorectal, lung cancers and lymphoma in the abatacept CDP were consistent with those in a comparable RA population. These data suggest no new safety signals with respect to malignancies, which will continue to be monitored.